2016
DOI: 10.1371/journal.pone.0165941
|View full text |Cite
|
Sign up to set email alerts
|

A Data Driven Network Approach to Rank Countries Production Diversity and Food Specialization

Abstract: The easy access to large data sets has allowed for leveraging methodology in network physics and complexity science to disentangle patterns and processes directly from the data, leading to key insights in the behavior of systems. Here we use country specific food production data to study binary and weighted topological properties of the bipartite country-food production matrix. This country-food production matrix can be: 1) transformed into overlap matrices which embed information regarding shared production o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…1 should be mainly attributed to the fact that eigenvectors of different order are considered in the two approaches. Hence, the two metrics bring different information; albeit different, this information is relevant for both metrics, as demonstrated by numerous practical applications of the two approaches [20][21][22]24,[30][31][32][33] .…”
Section: Resultsmentioning
confidence: 99%
“…1 should be mainly attributed to the fact that eigenvectors of different order are considered in the two approaches. Hence, the two metrics bring different information; albeit different, this information is relevant for both metrics, as demonstrated by numerous practical applications of the two approaches [20][21][22]24,[30][31][32][33] .…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, it has been shown that the degree sequence is responsible for the main characteristics of the trade network, such as the triangular structure of the biadjacency matrix between countries and products, see Fig. 8, [11][12][13][14][15][16][17]41] Using the BiCM as a filter permits to uncover structures of the network not explained by node degrees. The application of the BiCM to the ITN as a statistical null-model reveals communities of countries with similar economic development, namely developed, newly industrialized, and developing countries, and raw material (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, it has been shown that the degree sequence is responsible for the main characteristics of the trade network, such as the triangular structure of the biadjacency matrix between countries and products, see Fig. 8, [11][12][13][14][15][16][17]41] Using the BiCM as a filter permits to uncover structures of the network not explained by node degrees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally introduced to rank countries and products in the bipartite country-product export network [ 25 ], the fitness-complexity algorithm has been applied to diverse systems including ecological mutualistic networks [ 33 ], knowledge production networks [ 36 ], food production networks [ 37 ]. In its formulation for countries and products [ 25 ], the algorithm aims to find a vector of “fitness” scores for countries and “complexity” scores for products, respectively.…”
Section: Methodsmentioning
confidence: 99%